2021
DOI: 10.17762/turcomat.v12i2.2393
|View full text |Cite
|
Sign up to set email alerts
|

Motor-Imagery EEG Signals Classificationusing SVM, MLP and LDA Classifiers

Abstract: Electroencephalogram (EEG)signals based brain-computer interfacing (BCI) is the current technology trends in the field of rehabilitation robotic. This study compared the performance of support vector machine (SVM), linear discriminant analysis (LDA) and multi-layer perceptron (MLP) classifier with the combination of eight different features as a feature vector. EEG data were acquired from 20 healthy human subjects with predefined protocols. After the EEG signals acquisition, it was pre-processed followed by fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Table 2 compares the results of the proposed study with similar studies in recent years. The results showed that the OSVM had increased the accuracy of this model in detecting and classifying the type of MI by the differential evolution algorithm, thereby the accuracy of this method has increased compared to similar methods [Bashar SK et al 2015;Chai R et al 2012;Kim HS et al 2013;Temiyasathit C 2014;Chatterjee R, Bandyopadhyay T, 2016;Mebarkia K, Reffad A 2019;Narayan Y 2021]. Y Narayan (2021) showed that the SVM algorithm followed by the multi-layer perceptron (MLP) classifier had a high accuracy (98.8%) [Narayan Y 2021].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 compares the results of the proposed study with similar studies in recent years. The results showed that the OSVM had increased the accuracy of this model in detecting and classifying the type of MI by the differential evolution algorithm, thereby the accuracy of this method has increased compared to similar methods [Bashar SK et al 2015;Chai R et al 2012;Kim HS et al 2013;Temiyasathit C 2014;Chatterjee R, Bandyopadhyay T, 2016;Mebarkia K, Reffad A 2019;Narayan Y 2021]. Y Narayan (2021) showed that the SVM algorithm followed by the multi-layer perceptron (MLP) classifier had a high accuracy (98.8%) [Narayan Y 2021].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the OSVM had increased the accuracy of this model in detecting and classifying the type of MI by the differential evolution algorithm, thereby the accuracy of this method has increased compared to similar methods [Bashar SK et al 2015;Chai R et al 2012;Kim HS et al 2013;Temiyasathit C 2014;Chatterjee R, Bandyopadhyay T, 2016;Mebarkia K, Reffad A 2019;Narayan Y 2021]. Y Narayan (2021) showed that the SVM algorithm followed by the multi-layer perceptron (MLP) classifier had a high accuracy (98.8%) [Narayan Y 2021]. These results were close-knit, similar to our OSVM algorithm (F. , and Mebarkia K, Reffad A (2019) [Mebarkia K, Reffad A 2019] studies with 99.6%, 93.13%, and 94.11% accuracy, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, substantia researches showed that network properties can capture the synergistic effect of abnormal paroxysmal firing of neurons more effectively than the characteristics of single channel signals (Wang et al, 2015b ; Busche and Hyman, 2020 ; Gao et al, 2021 ). In addition, the combination of multiple features can help to display EEG abnormalities from various angles and improve the recognition efficiency (Mahato and Paul, 2020 ; Pei et al, 2020 ; Narayan, 2021 ; Wang et al, 2022 ). For instance, Narayan ( 2021 ) extracted and combined the features of AAR parameters, Barlow parameters, Hjorth parameters, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of studying the SEMG signals is to discriminate between various muscle movements into classes by MUAP during contractions [4]. These signals are detected and recorded using the surface electrodes which are placed adjacent to the skin superimposed on the muscles acupressure point [5]. The signal is generated during the contraction of the electrical activity of muscle fibers and the generated SEMG signals contain some useful feature which can be analyzed by the way of applying Wavelet Transform (WT) and other powerful techniques like Empirical Mode Decomposition (EMD) for multifunctional myoelectric control [6].…”
mentioning
confidence: 99%